Accounting for trust and control: Public sector partnerships in the arts. (June 2016) - ter Bogt, Henk; Tillema, Sandra
Abstract: This paper discusses the role of trust and accounting information in the control of public sector partnerships, in particular in partnerships in the arts. We present case research conducted in five theatres and municipalities in The Netherlands. Although autonomized, these theatres are still subsidised by the municipalities. Therefore, the municipalities have retained a certain degree of responsibility for the theatres. However, the low measurability of the theatres' outputs and outcomes complicates the municipalities' control as based on performance agreements and accounting information. This complication increases the role of trust. This study provides insight into the practices and processes underlying trust building and the supporting and mediating role accounting information plays here. Transparency and regular informal contacts between the theatres and their municipalities in combination with accounting documents, which 'discipline' the theatres, appear to be crucial in this respect. Furthermore, different hierarchical levels can be distinguished in the trust relationship. Trust first develops at the lower (operational) levels of an organisation, after which it progresses towards the higher organisational level. Finally, the research showed that the economically rational type of control as proposed by New Public Management did not really exist in our cases.